Ternary composite crystal form conversion accelerant and method for preparing ultrapure titanium dioxide by utilizing ternary composite crystal form conversion accelerant

By using a ternary composite crystal transformation promoter, and taking advantage of the synergistic effect of Sb-doped SnO2 crystals, Zn(NO3)2 aqueous solution and Nb2O5 powder, the phase transformation energy barrier of TiO2 was reduced, and ultrapure titanium dioxide was prepared by low-temperature calcination. This solved the problem of irreversible reconstruction of anatase phase TiO2 at high temperature and met the thermal stability requirements of high-end applications.

CN121342083APending Publication Date: 2026-01-16HUBEI TIANCI ELECTRONICS MATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202511892586.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-16
Publication Date
2026-01-16

AI Technical Summary

Technical Problem

In existing technologies, the anatase phase TiO2 undergoes irreversible reconstruction at high temperatures, causing optical parameters to drift with service temperature. This fails to meet the thermal stability requirements of high-end applications, and the phase transformation process requires high temperature and long duration to complete.

Method used

A ternary composite crystal transformation promoter, including Sb-doped SnO2 crystals, Zn(NO3)2 aqueous solution and Nb2O5 powder, was used to reduce the phase transition energy barrier of TiO2 through synergistic effect, thereby achieving the preparation of ultrapure titanium dioxide by low-temperature calcination.

Benefits of technology

The low-temperature transformation from anatase to rutile phase was achieved, and the calcination temperature was reduced to 820~860℃, resulting in the preparation of ultrapure titanium dioxide with uniform particle size and good anti-agglomeration properties, which meets the thermal stability requirements of high-end optical and dielectric applications.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a ternary composite crystal form conversion accelerant and a method for preparing ultra-pure titanium dioxide through the ternary composite crystal form conversion accelerant, and relates to the field of material preparation, the ternary composite crystal form conversion accelerant comprises a substance A, a Zn (NO3) 2 aqueous solution and Nb2O5 powder, the substance A is Sb-doped SnO2 crystals, the molar ratio of Sb / (Sn + Sb) is 3%-8%, and the molar fraction of Sb < 5 + > in all Sb elements is larger than or equal to 80%; the oxygen vacancy concentration of the substance A is 5 * 10 < 18 > cm <-3 > to 2 * 10 < 19 > cm <-3 >; the surface hydroxyl density of the substance A is 2.5 mmol / g to 4.0 mmol / g, and the free hydroxyl accounts for more than or equal to 70%; the Nb2O5 powder is in a monoclinic phase, the crystallinity is 65%-80%, and the specific surface area is 50 m < 2 > / g-80 m < 2 > / g. The ternary composite crystal form conversion accelerator can reduce the calcination temperature and realize low-temperature calcination to prepare ultra-pure titanium dioxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of materials preparation, and in particular to a ternary composite crystal form conversion promoter and a method for preparing ultrapure titanium dioxide using the ternary composite crystal form conversion promoter. Background Technology

[0002] In high-end applications such as optical coatings, high-k dielectric layers, and microwave dielectric devices, TiO2 is required to simultaneously provide high refractive index (n>2.7, 550nm) and high dielectric constant (ε>100) to reduce film thickness, decrease device size, and improve signal response speed. However, the room temperature refractive index of anatase TiO2 is approximately 2.54, and its dielectric constant is approximately 40. Furthermore, its lattice undergoes irreversible reconstruction above 600℃, causing optical parameters to drift with service temperature, failing to meet the stringent thermal stability requirements of precision optical systems. Therefore, achieving the transformation from anatase to rutile has become a critical technical problem urgently needing to be solved in the fields of optics and dielectric applications.

[0003] Existing technology indicates that during the phase transformation of TiO2, the content of the anatase phase begins to decrease from 700℃, while the content of the rutile phase begins to increase. The phase transformation is slow in the range of 700℃ to 900℃, but it accelerates above 900℃. This phase transformation can only be fully completed at 1000℃. Summary of the Invention

[0004] In view of this, this application provides a ternary composite crystal form conversion promoter and a method for preparing ultrapure titanium dioxide using the ternary composite crystal form conversion promoter. The ternary composite crystal form conversion promoter can reduce the calcination temperature at which TiO2 achieves complete conversion during the phase transformation process, thereby realizing the preparation of ultrapure titanium dioxide by low-temperature calcination.

[0005] Firstly, this application provides a ternary composite crystal transformation promoter, comprising: substance A, an aqueous solution of Zn(NO3)2, and Nb2O5 powder. It satisfies the following conditions: Condition I, substance A is an Sb-doped SnO2 crystal, with a molar ratio of Sb / (Sn+Sb) of 3%~8%. Condition II, the oxygen vacancy concentration of substance A (measured using electron paramagnetic resonance EPR) is 5 × 10⁻⁶. 18 ~2×10 19 cm -3 Furthermore, oxygen vacancies are mainly distributed on the crystal surface. Too low a concentration (below 5 × 10⁻⁶) 18 cm -3 Oxygen vacancies can lead to excessive rigidity of the SnO2 lattice, decreased interfacial compatibility with the TiO2 precursor, and increased nucleation energy barrier. Furthermore, excessively high concentrations (above 2 × 10⁻⁶) can also cause this. 19 cm -3Oxygen vacancies on the crystal surface can introduce excessive lattice distortion, disrupting lattice matching. Oxygen vacancies enriched on the crystal surface can serve as a substrate for Zn. 2+ The adsorption sites of Nb2O5 enable the ternary component to form a uniform coating layer on the surface of TiO2 particles. Condition III: The particle morphology of substance A is spherical, with an aspect ratio ≤1.2, and the proportion of secondary particles in the aggregates is ≤15%. This ternary composite crystal transformation promoter is a pre-prepared mixture. First, substance A and Nb2O5 powder are ball-milled and mixed, and then Zn(NO3)2 aqueous solution is added to form a slurry.

[0006] Primary grains refer to independent grains with clear boundaries and an aspect ratio ≤ 1.2, while secondary grains refer to aggregates with an aspect ratio > 1.5 that can be identified as consisting of ≥ 2 primary grains. Therefore, the proportion of secondary grains = (number of secondary grains / total number of grains) × 100%.

[0007] The ternary composite crystal transformation promoter of this application combines substance A, Zn(NO3)2 aqueous solution, and Nb2O5 powder. The synergistic effect of these three components lowers the phase transition energy barrier of TiO2 and prevents the introduction of impurities. Specifically, substance A is an Sb-doped SnO2 crystal, in which Sb replaces Sn in the SnO2 lattice. 4+ When the Sb molar ratio, i.e., Sb / (Sn+Sb), is between 3% and 8%, the free electron concentration of substance A can reach 3 × 10⁻⁶. 20 ~8×10 20 cm -3 The corresponding volume resistivity is ≤0.02Ω·cm. High conductivity can quickly dissipate static electricity generated by friction during stirring and homogenization of TiO2 precursor particles, preventing the formation of large agglomerates with a particle size >500nm. A Sb molar ratio that is too low (less than 3%) or too high (more than 8%) will enhance the adsorption force between particles, leading to the formation of large agglomerates. Furthermore, an Sb molar ratio within the above range is beneficial for the epitaxial growth of TiO2 rutile crystal nuclei on the surface of substance A, resulting in higher matching and more uniform TiO2 grain size. The oxygen vacancies in substance A are mainly distributed on the crystal surface, and the Sn at the oxygen vacancies... 2 + / Sn 4+ Zn can dissociate from Zn(NO3)2 aqueous solution due to the lack of electrons. 2+ This forms Sn-O-Zn coordination bonds and simultaneously forms Nb-OH groups on the surface of Nb2O5 powder, enabling Zn... 2+ Nb2O5 powder is uniformly loaded on the surface of material A, further preventing the formation of large agglomerates of TiO2 precursor particles during stirring and homogenization.

[0008] Furthermore, further restricting the particle morphology of substance A to near-spherical, with a D50 ≤ 60 nm, aspect ratio ≤ 1.2, and secondary particles accounting for ≤ 15% of the aggregates, can reduce the packing gaps between particles, allowing Zn to... 2+ The Nb2O5 powder forms a monolayer coating on its surface, providing a stable contact basis for the subsequent interfacial reaction with the TiO2 precursor slurry (anatase phase TiO2 hydrated slurry). This facilitates the preparation of ultrapure electronic-grade titanium dioxide with a particle size D50 of 0.3~0.7μm and an anti-agglomeration index ≥0.85.

[0009] In some embodiments, the concentration of the Zn(NO3)2 aqueous solution is 0.5~2.0 mol / L, wherein the Fe content is <1 ppm and the Cl content is <1 ppm. - Content <0.5ppm. And / or, the Nb₂O₅ powder is a monoclinic phase with a crystallinity of 65%~80% and a specific surface area of ​​50~80m². 2 / g. If the crystallinity of Nb₂O₅ powder is too low (below 65%), there will be too much disordered phase, and it will undergo sticky sintering at calcination temperatures above 800℃, which is detrimental to the transformation from anatase to rutile. If the crystallinity of Nb₂O₅ powder is too high (above 80%), there will be insufficient surface active sites, which is also not conducive to the transformation from anatase to rutile at low temperatures. Zn 2+ Ti in TiO2 4+ With similar radii, ion doping can be introduced into the TiO2 anatase lattice to form a slight lattice distortion, thereby reducing the migration energy barrier of atoms in the TiO2 lattice. This lowers the activation energy for the transformation from the anatase phase to the rutile phase from 280 kJ / mol in the traditional process to below 220 kJ / mol (estimated by differential scanning calorimetry DSC). The Lewis acid sites on the surface of monoclinic Nb2O5 powder can adsorb Ti(OH)2 from the TiO2 precursor (anatase phase TiO2). 2+ Ions weaken the Ti-O bond strength, promoting the formation of Ti(OH)2 2+ Dehydration forms TiO2 crystal nuclei, Zn 2+ The introduced lattice distortion provides a directional channel for the growth of crystal nuclei, allowing TiO2 crystal nuclei to preferentially grow along the

[110] crystal orientation of the rutile phase, thus avoiding the residue of the anatase phase. Therefore, the synergistic effect of substances A, Zn(NO3)2 aqueous solution and Nb2O5 can achieve the preparation of ultrapure titanium dioxide by low-temperature calcination (820~860℃).

[0010] In some embodiments, the molar ratio of Sn, Zn, and Nb is 1:(0.45~0.55):(0.08~0.12), which is the molar ratio of the feed materials. This results in a better synergistic effect among the three elements, making it easier to achieve the preparation of ultrapure titanium dioxide by low-temperature calcination, and obtaining a product with a purity ≥99.9%.

[0011] In some embodiments, the main phase of substance A is rutile SnO2, which can provide an epitaxial template with a BET specific surface area of ​​60-120 m². 2 Substance A has a mesopore size distribution of 8–20 nm, with mesopore volume accounting for 70%–90% of the total pore volume, and a pore volume ≥ 0.3 cm³. 3 / g. The Sb content in the crystals of substance A 5+ The molar fraction of Sb is ≥80% to ensure the integrity of the SnO2 crystal lattice and controllable oxygen vacancy concentration. The surface hydroxyl density of substance A is 2.5~4.0 mmol / g, and the proportion of free hydroxyl groups is ≥70%. This facilitates the transformation of anatase SnO2 into rutile SnO2 at low temperatures.

[0012] Preparation method of substance A: Step 1: Obtain an ethanol solution containing SnCl4 and SbCl5, denoted as solution a, where the molar ratio of Sb / (Sn+Sb) in solution a is 3%~8%; Solution a: Mix 0.5 mol / L SnCl4·5H2O and SbCl5 ethanol solution, and then dilute to volume with anhydrous ethanol until the molar ratio of Sb / (Sn+Sb) is 3%~8%; Step 2: Obtain an ethanol solution containing urea, denoted as solution b; Solution b: 1.0 mol / L urea diluted to volume with anhydrous ethanol; Step 3: Obtain a mixed solution of solution a and solution b, stir at room temperature for 10-15 minutes, reflux at 80-90℃ for 1-2 hours, and then put it into a high-pressure reactor and keep it at 110-120℃ for 10-12 hours to obtain a white wet gel.

[0013] Solution a and solution b were mixed at a volume ratio of 1:1, stirred at 25°C for 10-15 minutes, refluxed at 80°C for 2 hours, and then placed in a high-pressure reactor and kept at 120°C for 12 hours to obtain a white wet gel.

[0014] Step 4: Treat the white wet gel at 55~65℃ with O3 / UV for 30~40 min, then vacuum dry at 70~80℃ for 10~12 h to obtain dry gel. Calcine the dry gel at 500~600℃ at a rate of 1.5~2℃ / min in air atmosphere for 1~2 h, and then allow it to cool naturally.

[0015] Steps 1 to 4 facilitate the preparation of substance A, whose main phase is rutile SnO2, and whose BET specific surface area, mesopore size distribution, mesopore volume ratio, and pore volume are all within a suitable range. The white wet gel was treated at 60℃ with O3 / UV (5 g / h ozone, 30 W UV lamp) for 30 min, then vacuum dried at 80℃ for 12 h to obtain a dry gel. The dry gel was then heated to 550℃ at a rate of 2℃ / min and calcined in air for 2 h, followed by natural cooling.

[0016] Step 5: Disperse the calcined powder in deionized water with a solid content of 30-40%, mill it with 0.3-0.5 mm ZrO2 beads for 15-30 min, then centrifuge at 2000-3000 rpm for 3-5 min and dry it.

[0017] The calcined powder, with a solid content of 30-40%, was dispersed in deionized water and milled with 0.3-0.5 mm ZrO2 beads for 15-30 min. It was then centrifuged at 2000-3000 rpm for 3-5 min and dried (inlet temperature 160-180℃, outlet temperature 80-95℃) to obtain a powder with a D50 of 45-55 nm. After vacuum dehydration at 120℃ for 2 h, the powder was placed in a DBD plasma reactor (50 W, 15 min, 3000 ppm H2O / O2 / Ar) at a discharge power of 50 W for 15-20 min to obtain the final product.

[0018] In some embodiments, the pH of the Zn(NO3)2 aqueous solution is 1.5 to 2.5, and SO42-... 2- Na + K + Each component contains less than 1 ppm. This is beneficial for Zn. 2+ It penetrates uniformly in the form of single ions, which is beneficial to improving the purity of the product.

[0019] In some embodiments, the composite crystal form conversion promoter composition has an anti-agglomeration index ≥0.85 after standing at 25°C and 50%RH for 24 hours.

[0020] Secondly, this application provides a method for preparing ultrapure electronic-grade titanium dioxide, comprising at least the following steps: Step I: Obtain anatase TiO2 hydrated slurry with a solid content of 25wt% to 35wt% and a pH of 1.5 to 2.0 (obtained by hydrolysis-hydrothermal crystallization of tetrabutyl titanate, D50 < 100nm). Step II: Add the above-mentioned ternary composite crystal transformation promoter and surface additive to the anatase phase TiO2 hydrated slurry in sequence, and homogenize it for 10 min to 30 min at a shear rate of linear velocity ≥4 m / s under the condition that the temperature is not higher than 90 ℃. Step III: After filtration and drying, calcination is carried out at 820°C to 860°C in an oxidizing atmosphere for 3 to 4 hours.

[0021] In some embodiments, after the homogenization treatment in step II, the median particle size D50 of the slurry is ≤200nm, and the coating coverage of Zn, Nb and Sn elements on the surface of TiO2 particles is ≥80%.

[0022] In some embodiments, the surface additives include polyethylene glycol-600, and the settling rate of Nb2O5 powder in anatase TiO2 hydrated slurry after standing for 24 hours is ≤0.5% / h.

[0023] In some embodiments, in step III, the drying is carried out by spray drying, with an inlet temperature of 180~220°C and an outlet temperature of 80~90°C. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0025] A ternary composite crystal transformation promoter The mixture includes: substance A, an aqueous solution of Zn(NO3)2, and Nb2O5 powder, and satisfies at least one of the following conditions: Condition I: Substance A is an Sb-doped SnO2 crystal, and the molar ratio of Sb / (Sn+Sb) is 3%~8%. Condition II: The oxygen vacancy concentration of substance A is 5×10⁻⁶. 18 cm -3 Up to 2×10 19 cm -3 Furthermore, oxygen vacancies are distributed on the crystal surface. Condition III: The particles of substance A have a spherical morphology with an aspect ratio ≤1.2, and the proportion of secondary particles in the aggregates is ≤15%. For example, the molar ratio of Sb / (Sn+Sb) is 3%, 4%, 5%, 6%, 7%, 8%, or any two of the above values. For example, the oxygen vacancy concentration of substance A is 5 × 10⁻⁶. 18 cm -3 6×10 18 cm -3 7×10 18 cm -3 8×10 18 cm -3 9×10 18 cm -3 1×10 19 cm -3 2×1019 cm -3 Or the range between any two of the above values.

[0026] In some embodiments, the concentration of the Zn(NO3)2 aqueous solution is from 0.5 mol / L to 2.0 mol / L, wherein the Fe content is <1 ppm and the Cl content is <1 ppm. - The content is <0.5 ppm. For example, the concentration of the Zn(NO3)2 aqueous solution is 0.5 mol / L, 0.6 mol / L, 0.8 mol / L, 1.0 mol / L, 1.5 mol / L, 1.8 mol / L, 2.0 mol / L or any two of the above values.

[0027] In some embodiments, the Nb₂O₅ powder is a monoclinic phase with a crystallinity of 65% to 80% and a specific surface area of ​​50 m². 2 / g to 80m 2 / g. For example, the crystallinity of the Nb2O5 powder is 65%, 68%, 70%, 72%, 75%, 78%, 80%, or any two of the above values.

[0028] In some embodiments, the molar ratio of Sn, Zn, and Nb is 1:(0.45~0.55):(0.08~0.12). Preferably, the molar ratio of Sn, Zn, and Nb is 1:0.5:0.1.

[0029] In some embodiments, the main phase of substance A is rutile SnO2, with a BET specific surface area of ​​60 m². 2 / g to 120m 2 / g, and D50≤60nm. For example, the BET specific surface area of ​​substance A is 60m². 2 / g、70m 2 / g、80m 2 / g、90m 2 / g, 100m 2 / g、110m 2 / g, 120m 2 / g or the range between any two of the above values.

[0030] In some embodiments, the mesopore size distribution of substance A is 8 nm to 20 nm, the mesopore volume accounts for 70% to 90% of the total pore volume, and the pore volume is ≥0.3 cm³. 3 / g. For example, the mesopore size distribution of substance A is 8nm, 10nm, 12nm, 14nm, 16nm, 18nm, 20nm, or any two of the above values. For example, the mesopore volume of substance A accounts for 70%, 75%, 80%, 85%, 90% of the total pore volume, or any two of the above values.

[0031] In some embodiments, Sb in the crystal of substance A 5+ The molar fraction of Sb in substance A is ≥80%, the surface hydroxyl density of substance A is 2.5 mmol / g to 4.0 mmol / g, and the proportion of free hydroxyl groups is ≥70%. For example, the surface hydroxyl density of substance A is 2.5 mmol / g, 2.8 mmol / g, 3.0 mmol / g, 3.5 mmol / g, 4.0 mmol / g, or any two of the above values.

[0032] In some embodiments, the pH of the Zn(NO3)2 aqueous solution is 1.5 to 2.5, and SO42-... 2- Na + K + Each component contains less than 1 ppm. The pH value of the Zn(NO3)2 aqueous solution is 1.5, 1.8, 2.0, 2.2, 2.5 or any two of the above values.

[0033] In some embodiments, the composite crystal form conversion promoter composition has an anti-agglomeration index ≥0.85 after standing at 25°C and 50%RH for 24 hours.

[0034] A method for preparing ultrapure electronic-grade titanium dioxide At least the following steps are included: Step I: Obtain anatase TiO2 hydrated slurry with a solid content of 25wt% to 35wt% and a pH of 1.5 to 2.0. For example, the solid content of the anatase TiO2 hydrated slurry is 25wt%, 28wt%, 30wt%, 32wt%, 35wt%, or any two of the above values.

[0035] Step II: Add the above-mentioned ternary composite crystal transformation promoter and surface additive sequentially to the anatase phase TiO2 hydrated slurry, and homogenize it at a shear rate of ≥4 m / s for 10 min to 30 min at a temperature not exceeding 90 °C. For example, the homogenization time is 10 min, 12 min, 14 min, 15 min, 16 min, 18 min, 20 min, 25 min, 30 min, or any two of the above values.

[0036] Step III: After filtration and drying, calcination is carried out at 820°C to 860°C in an oxidizing atmosphere for 3 to 4 hours. For example, the calcination temperature is 820°C, 830°C, 840°C, 850°C, 860°C, or any two of the above values.

[0037] In some embodiments, after the homogenization process in step II, the median particle size D50 of the slurry is ≤200nm, and the coating coverage of Zn, Nb, and Sn elements on the surface of TiO2 particles is ≥80%. For example, the median particle size D50 of the slurry is 40nm, 50nm, 60nm, 80nm, 100nm, 120nm, 150nm, 180nm, 200nm, or a range between any two of the above values.

[0038] In some embodiments, the surface additives include polyethylene glycol-600, and the settling rate of Nb2O5 powder in anatase TiO2 hydrated slurry after standing for 24 hours is ≤0.5% / h.

[0039] In some embodiments, in step III, drying is performed using spray drying, with an inlet temperature of 180-220°C and an outlet temperature of 80-90°C. Exemplarily, the inlet temperature is 180°C, 190°C, 200°C, 210°C, 220°C, or any two of the above values. The outlet temperature is 80°C, 82°C, 84°C, 85°C, 88°C, 90°C, or any two of the above values.

[0040] The following specific embodiments illustrate a method for preparing ultrapure electronic-grade titanium dioxide based on a ternary composite crystal form conversion promoter and using the ternary composite crystal form conversion promoter. Those skilled in the art will understand that the preparation method described in this application is merely an example, and any other suitable preparation method is within the scope of this application. Example 1

[0041] Step I: Raw material preparation (1) Substance A Solution a: Mix 0.5 mol / L SnCl4·5H2O and SbCl5 ethanol solution, then dilute to volume with anhydrous ethanol to a molar ratio of Sb / (Sn+Sb) of 5%; Solution b: 1.0 mol / L urea diluted to volume with anhydrous ethanol; Solution a and solution b were mixed at a volume ratio of 1:1, stirred at 25°C for 10 min, refluxed at 80°C for 2 h, and then placed in a high-pressure reactor and kept at 120°C for 12 h to obtain a white wet gel.

[0042] The white wet gel was treated with O3 / UV (5 g / h ozone, 30 W UV lamp) at 60℃ for 30 min, then vacuum dried at 80℃ for 12 h to obtain the dry gel. The dry gel was then calcined at 550℃ at a rate of 2℃ / min in air for 2 h, naturally cooled, and sampled for testing. Electron paramagnetic resonance (EPR) testing showed that Sb 5+ It accounts for 88% of the total Sb mole fraction, and the oxygen vacancy concentration is 7.7 × 10⁻⁶. 18 cm -3 The discharge test showed that the specific surface area of ​​BET was 98 m². 2 / g, mesopore pore size is 12nm, mesopore volume accounts for 78% of the total pore volume, and the total pore volume is 0.36cm³. 3 / g.

[0043] The calcined powder was dispersed in deionized water at a solid content of 30%, milled with 0.3 mm ZrO2 beads for 30 min, then centrifuged at 3000 rpm for 5 min, and dried (inlet 180℃, outlet 80℃) to obtain a powder with a D50 of 52 nm, an aspect ratio of 1.08, and a secondary particle content of 8%. After vacuum dehydration at 120℃ for 2 h, the powder was placed in a DBD plasma reactor (50 W, 15 min, 3000 ppm H2O / O2 / Ar) and treated at a discharge power of 50 W for 15 min. The surface hydroxyl density was 3.4 mmol / g, and the free hydroxyl content was 74%.

[0044] (2) Preparation of Nb2O5 powder Electronic grade NbCl5 (Fe < 0.1 ppm) was added dropwise to deionized water at 0°C to form a transparent Nb(OH)5 sol. The pH was adjusted to 9 with ammonia, resulting in a white Nb(OH)5 precipitate. The precipitate was then filtered and washed until Cl... - <0.5 ppm, after vacuum drying at 80℃, the temperature was increased to 450℃ at 5℃ / min and held for 2 hours to obtain amorphous Nb2O5. The amorphous Nb2O5 was then increased to 650℃ at 2℃ / min and held for 1 hour to obtain a crystallinity of 72% and a specific surface area of ​​65 m². 2 / g of monoclinic Nb2O5 powder.

[0045] Step II: Pre-preparation of ternary composite crystal form conversion promoter Ball milling dry mixing: The substance A obtained in step I and Nb2O5 powder were loaded into a polyurethane ball mill jar at a ratio of n(Sn):n(Nb)=1:0.1. Zirconia grinding beads with a diameter of 0.3 mm were used to grind the mixture in a planetary ball mill at a speed of 400 rpm for 30 min under argon protection.

[0046] Slurry preparation: Maintain the slurry solids content at 30 wt%, and slowly add 2.0 mol / L electronic grade Zn(NO3)2 solution (pH 1.8, Fe < 0.3 ppm, Cl) dropwise to the ball mill jar. - <0.2 ppm, SO4 2- Na + K + (All <0.5 ppm) until the molar ratio of Zn to Sn reaches 0.50:1.0, continue ball milling for 15 min to obtain a wet pre-mixed mixture.

[0047] Step III: Preparation of anatase TiO2 hydrated slurry Tetrabutyl titanate was added dropwise to deionized water and hydrothermally reacted at 180°C for 6 hours. After cooling, it was diluted with deionized water to obtain a hydrated slurry with a solid content of 30 wt% and a pH of 1.7. The D0 was measured using a laser particle size analyzer. 50 = 82nm, XRD shows anatase phase ≥99%.

[0048] Step IV: Homogenization and Low-Temperature Conversion A wet premixed material was added at a Sn:Ti ratio of 1:100, along with 0.5 wt% PEG-600. The mixture was homogenized at 85℃ and a linear velocity of 8 m / s for 20 min, resulting in a median particle size (D50) of 156 nm. XPS analysis revealed surface atomic ratios of Zn / Ti = 0.14, Nb / Ti = 0.023, and Sn / Ti = 0.025. Therefore, the coating coverage of Zn, Nb, and Sn elements on the TiO2 particle surface was 83%.

[0049] Spray drying: inlet temperature 200 ℃, outlet temperature 85 ℃, powder moisture content 0.6 wt%.

[0050] The spray-dried powder was calcined at 840 °C for 4 hours in an atmosphere of 95 vol % air and 5 vol % O2, with a heating rate of 5 °C / min, and then naturally cooled to room temperature to obtain the product (powder W).

[0051] Expected results: The X-ray diffraction (XRD) pattern of powder W showed only rutile characteristic peaks, with a rutile phase content of approximately 98% and almost no detectable anatase residue. GDMS analysis showed that the total amount of impurities such as iron, sodium, potassium, sulfur, and chlorine was less than 5 ppm, corresponding to a purity of over 99.995%. Laser particle size analysis (wet method, 0.1~1000µm) indicated that the powder's median volume diameter D... 50 Approximately 0.48µm, D 90 The particle size is 0.71µm, therefore, the particle size distribution is narrow and there are no obvious large agglomerations.

[0052] Anti-agglomeration index test: Take 5.0 g of spray-dried powder, let it stand at 25℃ and 50%RH for 24 h, add 40 mL of deionized water, sonicate for 5 min, inject into a wet laser particle size analyzer, measure 3 times consecutively, and take the average D'. 50 Let it be D 50 ,re; The same batch of spray-dried powder, ultrasonicated for 5 min, yields D 50 Anti-agglomeration index = D' 50 / D 50 =0.88. Therefore, it meets the electronic grade requirements. It can be seen that the relevant parameters of substance A, Zn(NO3)2 aqueous solution and Nb2O5 powder can synergistically achieve the preparation of ultrapure rutile phase titanium dioxide by low-temperature calcination (820~860℃) when the parameters are within a suitable range. Furthermore, by properly controlling the D50 value, particle morphology, aspect ratio and proportion of secondary particles of substance A, it is beneficial to prepare electronic grade ultrapure rutile phase titanium dioxide. Example 2

[0053] Step I: Raw material preparation (1) Substance A Solution a: Mix 0.5 mol / L SnCl4·5H2O and SbCl5 ethanol solution, then dilute to volume with anhydrous ethanol to a molar ratio of Sb / (Sn+Sb) of 5%; Solution b: 1.0 mol / L urea diluted to volume with anhydrous ethanol; Solution a and solution b were mixed at a volume ratio of 1:1, stirred at 25°C for 10 min, refluxed at 80°C for 2 h, and then placed in a high-pressure reactor and kept at 120°C for 12 h to obtain a white wet gel.

[0054] The white wet gel was treated with O3 / UV (5 g / h ozone, 30 W UV lamp) at 60℃ for 30 min, then vacuum dried at 80℃ for 12 h to obtain the dry gel. The dry gel was then calcined at 550℃ at a rate of 2℃ / min in air for 2 h, naturally cooled, and sampled for testing. Electron paramagnetic resonance (EPR) testing showed that Sb 5+ It accounts for 88% of the total Sb mole fraction, and the oxygen vacancy concentration is 7.7 × 10⁻⁶. 18 cm -3 The discharge test showed that the specific surface area of ​​BET was 98 m². 2 / g, mesopore pore size is 12nm, mesopore volume accounts for 78% of the total pore volume, and the total pore volume is 0.36cm³. 3 / g.

[0055] The calcined powder was dispersed in deionized water with a solid content of 40%, milled with 0.5 mm ZrO2 beads for 15 min, then centrifuged at 2000 rpm for 3 min, and dried (inlet 180℃, outlet 95℃) to obtain a powder with a D50 of 68 nm, an aspect ratio of 1.25, and a secondary particle content of 18%. After vacuum dehydration at 120℃ for 2 h, the powder was placed in a DBD plasma reactor (50 W, 15 min, 3000 ppm H2O / O2 / Ar) and treated at a discharge power of 50 W for 15 min. The surface hydroxyl density was 3.4 mmol / g, and the free hydroxyl content was 74%.

[0056] (3) Preparation of Nb2O5 powder Electronic grade NbCl5 (Fe < 0.1 ppm) was added dropwise to deionized water at 0°C to form a transparent Nb(OH)5 sol. The pH was adjusted to 9 with ammonia, resulting in a white Nb(OH)5 precipitate. The precipitate was then filtered and washed until Cl... - <0.5 ppm, after vacuum drying at 80℃, the temperature was increased to 450℃ at 5℃ / min and held for 2 hours to obtain amorphous Nb2O5. The amorphous Nb2O5 was then increased to 650℃ at 2℃ / min and held for 1 hour to obtain a crystallinity of 72% and a specific surface area of ​​65 m². 2 / g of monoclinic Nb2O5 powder.

[0057] Step II: Pre-preparation of ternary composite crystal form conversion promoter Ball milling dry mixing: The substance A obtained in step I and Nb2O5 powder were loaded into a polyurethane ball mill jar at a ratio of n(Sn):n(Nb)=1:0.1. Zirconia grinding beads with a diameter of 0.3 mm were used to grind the mixture in a planetary ball mill at a speed of 400 rpm for 30 min under argon protection.

[0058] Slurry preparation: Maintain the slurry solids content at 30 wt%, and slowly add 2.0 mol / L electronic grade Zn(NO3)2 solution (pH 1.8, Fe < 0.3 ppm, Cl) dropwise to the ball mill jar. - <0.2 ppm, SO4 2- Na + K + (All <0.5 ppm) until the molar ratio of Zn to Sn reaches 0.50:1.0, continue ball milling for 15 min to obtain a wet pre-mixed mixture.

[0059] Step III: Preparation of anatase TiO2 hydrated slurry Tetrabutyl titanate was added dropwise to deionized water and hydrothermally reacted at 180°C for 6 hours. After cooling, it was diluted with deionized water to obtain a hydrated slurry with a solid content of 35 wt% and a pH of 1.7. The D0 was measured using a laser particle size analyzer. 50= 82nm, XRD shows anatase phase ≥99%.

[0060] Step IV: Homogenization and Low-Temperature Conversion The wet premixed material was added at a molar ratio of Sn:Ti = 1:100, and 0.5 wt% PEG-600 was added. The mixture was homogenized at 85℃ and a linear velocity of 8 m / s for 20 min. The median particle size D50 of the slurry was 156 nm.

[0061] Spray drying: inlet temperature 200 ℃, outlet temperature 85 ℃, powder moisture content 0.6 wt%.

[0062] The spray-dried powder was calcined at 840 °C for 4 hours in an atmosphere of 95 vol % air and 5 vol % O2, with a heating rate of 5 °C / min, and then naturally cooled to room temperature to obtain the product.

[0063] Test results: The X-ray diffraction (XRD) pattern of W showed only rutile characteristic peaks, with a rutile phase content of approximately 98% and almost no anatase residue. GDMS analysis showed that the total amount of impurities such as iron, sodium, potassium, sulfur, and chlorine was less than 5 ppm, corresponding to a purity of over 99.995%. Anti-agglomeration index test: 5.0 g of spray-dried powder was taken, allowed to stand at 25℃ and 50%RH for 24 h, 40 mL of deionized water was added, and the mixture was sonicated for 5 min. The sample was then injected into a wet laser particle size analyzer, and the result was measured three times consecutively. The average value was recorded as D'. 50 The same batch of spray-dried powder, ultrasonicated for 5 minutes, yielded D. 50 Anti-agglomeration index = D' 50 / D 50 =0.82. At this point, hard agglomerates form grain boundary bridging during calcination, resulting in a decrease in resistivity and substandard electronic-grade insulation performance.

[0064] Comparative Example

[0065] Step I: Raw material preparation (1) Substance A Solution a: Mix 0.5 mol / L SnCl4·5H2O and SbCl5 ethanol solution, and then dilute to volume with anhydrous ethanol to a molar ratio of Sb / (Sn+Sb) of 2%; Solution b: 1.0 mol / L urea diluted to volume with anhydrous ethanol; Solution a and solution b were mixed at a volume ratio of 1:1, stirred at 25°C for 10 min, refluxed at 80°C for 2 h, and then placed in a high-pressure reactor and kept at 120°C for 12 h to obtain a white wet gel.

[0066] The white wet gel was treated with O3 / UV (5 g / h ozone, 30 W UV lamp) at 60℃ for 30 min, and then vacuum dried at 80℃ for 12 h to obtain a dry gel. The dry gel was heated to 550℃ at 2℃ / min and calcined in air for 2 h, then naturally cooled and sampled for testing. Electron paramagnetic resonance (EPR) test: Sb 5+ It accounts for 73% of the total Sb mole fraction, and the oxygen vacancy concentration is 4.8 × 10⁻⁶. 18 cm -3 The discharge test showed that the specific surface area of ​​BET was 98 m². 2 / g, mesopore pore size is 12nm, mesopore volume accounts for 78% of the total pore volume, and the total pore volume is 0.36cm³. 3 / g.

[0067] The calcined powder was dispersed in deionized water with a solid content of 30%, milled with 0.3 mm ZrO2 beads for 30 min, then centrifuged at 3000 rpm for 5 min, and dried (inlet 180℃, outlet 80℃) to obtain a powder with a D50 of 52 nm, an aspect ratio of 1.08, and a secondary particle content of 8%. After vacuum dehydration at 120℃ for 2 h, the powder was placed in a DBD plasma reactor (50 W, 15 min, 3000 ppm H2O / O2 / Ar) at a discharge power of 50 W for 15 min. The surface hydroxyl density was 3.4 mmol / g, and the free hydroxyl content was 74%.

[0068] (4) Preparation of Nb2O5 powder Electronic grade NbCl5 (Fe < 0.1 ppm) was added dropwise to deionized water at 0°C to form a transparent Nb(OH)5 sol. The pH was adjusted to 9 with ammonia, resulting in a white Nb(OH)5 precipitate. The precipitate was then filtered and washed until Cl... - <0.5 ppm, after vacuum drying at 80℃, the temperature was increased to 450℃ at 5℃ / min and held for 2 hours to obtain amorphous Nb2O5. The amorphous Nb2O5 was then increased to 650℃ at 2℃ / min and held for 1 hour to obtain a crystallinity of 72% and a specific surface area of ​​65 m². 2 / g of monoclinic Nb2O5 powder.

[0069] Step II: Pre-preparation of ternary composite crystal form conversion promoter Ball milling dry mixing: The substance A obtained in step I and Nb2O5 powder were loaded into a polyurethane ball mill jar at a ratio of n(Sn):n(Nb)=1:0.1. Zirconia grinding beads with a diameter of 0.3 mm were used to grind the mixture in a planetary ball mill at a speed of 400 rpm for 30 min under argon protection.

[0070] Slurry preparation: Maintain the slurry solids content at 30 wt%, and slowly add 2.0 mol / L electronic grade Zn(NO3)2 solution (pH 1.8, Fe < 0.3 ppm, Cl) dropwise to the ball mill jar. - <0.2 ppm, SO4 2- Na + K + (All <0.5 ppm) until the molar ratio of Zn to Sn reaches 0.50:1.0, continue ball milling for 15 min to obtain a wet pre-mixed mixture.

[0071] Step III: Preparation of anatase TiO2 hydrated slurry Tetrabutyl titanate was added dropwise to deionized water and hydrothermally reacted at 180°C for 6 hours. After cooling, it was diluted with deionized water to obtain a hydrated slurry with a solid content of 30 wt% and a pH of 1.7. The D0 was measured using a laser particle size analyzer. 50 = 82nm, XRD shows anatase phase ≥99%.

[0072] Step IV: Homogenization and Low-Temperature Conversion A wet premixed material was added at a Sn:Ti ratio of 1:100, along with 0.5 wt% PEG-600. The mixture was homogenized at 85℃ and a linear velocity of 8 m / s for 20 min, resulting in a median particle size (D50) of 156 nm. XPS analysis revealed surface atomic ratios of Zn / Ti = 0.14, Nb / Ti = 0.023, and Sn / Ti = 0.025. Therefore, the coating coverage of Zn, Nb, and Sn elements on the TiO2 particle surface was 83%.

[0073] Spray drying: inlet temperature 200 ℃, outlet temperature 85 ℃, powder moisture content 0.6 wt%.

[0074] The spray-dried powder was calcined at 840 °C for 4 hours in an atmosphere of 95 vol % air and 5 vol % O2, with a heating rate of 5 °C / min, and then naturally cooled to room temperature to obtain the powder.

[0075] Test results: The X-ray diffraction (XRD) pattern of the powder showed characteristic peaks of rutile and anatase, with the rutile phase content being only about 38%.

[0076] The above are merely preferred embodiments of this application and are not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A ternary composite crystal transformation promoter, characterized in that, include: Substance A, Zn(NO3)2 aqueous solution and Nb2O5 powder; And it meets the following conditions: Condition I: Substance A is an Sb-doped SnO2 crystal, with a Sb / (Sn+Sb) molar ratio of 3%~8%, and Sb 5+ It accounts for ≥80% of the total mole fraction of Sb; Condition II: The oxygen vacancy concentration of substance A is 5 × 10⁻⁶. 18 cm -3 Up to 2×10 19 cm -3 ; Condition III: The surface hydroxyl density of substance A is 2.5 mmol / g to 4.0 mmol / g, and the proportion of free hydroxyl groups is ≥70%; Condition IV: The Nb₂O₅ powder is a monoclinic phase with a crystallinity of 65% to 80% and a specific surface area of ​​50 m². 2 / g to 80m 2 / g.

2. The ternary composite crystal transformation promoter according to claim 1, characterized in that, The concentration of the Zn(NO3)2 aqueous solution is from 0.5 mol / L to 2.0 mol / L, wherein the Fe content is <1 ppm and the Cl content is <1 ppm. - Content <0.5ppm; The oxygen vacancies of the substance A are distributed on the crystal surface.

3. The ternary composite crystal transformation promoter according to claim 1 or 2, characterized in that, The molar ratio of Sn, Zn, and Nb is 1: (0.45~0.55): (0.08~0.12).

4. The ternary composite crystal transformation promoter according to claim 1, characterized in that, The main phase of substance A is rutile SnO2, and its BET specific surface area is 60 m². 2 / g to 120m 2 / g, and D50≤60nm; The mesopore size distribution of substance A is 8 nm to 20 nm, the mesopore volume accounts for 70% to 90% of the total pore volume, and the pore volume is ≥0.3 cm³. 3 / g; The particles of substance A are spherical in shape with an aspect ratio of ≤1.2, and the proportion of secondary particles in the aggregates is ≤15%.

5. The ternary composite crystal transformation promoter according to claim 1, characterized in that, The pH value of the Zn(NO3)2 aqueous solution is 1.5 to 2.5, and SO42- 2- Na + K + Each content is <1ppm.

6. The ternary composite crystal transformation promoter according to claim 4, characterized in that, The composite crystal form conversion promoter composition has an anti-agglomeration index ≥0.85 after standing at 25°C and 50%RH for 24 hours.

7. A method for preparing ultrapure titanium dioxide using the ternary composite crystal transformation promoter according to any one of claims 1 to 6, characterized in that, The method includes at least the following steps: Step I: Obtain anatase TiO2 hydrated slurry with a solid content of 25wt% to 35wt% and a pH of 1.5 to 2.0; Step II: Add the ternary composite crystal transformation promoter and surface additive to the anatase phase TiO2 hydrated slurry in sequence, and homogenize it for 10 min to 30 min at a shear rate of linear velocity ≥4 m / s under the condition that the temperature is not higher than 90 ℃. Step III: After filtration and drying, calcine at 820°C to 860°C in an oxidizing atmosphere for 1 to 2 hours.

8. The method according to claim 7, characterized in that, After homogenization in step II, the median particle size D50 of the slurry is ≤200nm, and the coating coverage of Zn, Nb and Sn elements on the surface of TiO2 particles is ≥80%.

9. The method according to claim 7, characterized in that, The surface additive includes polyethylene glycol-600; The Nb2O5 powder settles at a rate of ≤0.5% / h after standing in the anatase phase TiO2 hydrated slurry for 24 hours.

10. The method according to claim 7, characterized in that, In step III, the drying is carried out by spray drying, with an inlet temperature of 180~220℃ and an outlet temperature of 80~90℃.

Citation Information

Patent Citations

  • Method for preparing rutile titanium dioxide

    CN101613124A

  • Production method of non-coating rutile type titanium dioxide

    CN109607608A

  • Sulfuric acid method for preparing high-specific-surface-area high-purity rutile titanium dioxide

    CN111573719A

  • Production method of high-purity electronic-grade titanium dioxide

    CN117699848A

  • Application of rutile-doped titanium dioxide as wave-absorbing material

    CN118419971A